If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3y-7=-35
We move all terms to the left:
-3y-7-(-35)=0
We add all the numbers together, and all the variables
-3y+28=0
We move all terms containing y to the left, all other terms to the right
-3y=-28
y=-28/-3
y=9+1/3
| 95=–5(t+16) | | 1.9x-24=1.3x+6 | | 5x+65=10x+45 | | 1.2=1/2(-9.8)(t | | 6b+8=68 | | 5y-6=13y+5 | | 3n-2n+1n=5 | | –3v+–4=8 | | 10a-9=41 | | 10q=7-3q | | -2x–13=-3x–5 | | 25x+30=65x+20) | | 13=y/6.25+8 | | 3x-6/3+9=14 | | 60=6x+30 | | 8b+88=144 | | 5x-4+1x=20 | | 7x-63=133 | | 2n-5n=-15 | | -5/9x-2/45x+1/5x=-54 | | 9x-21=3x-15 | | 6(4r+1)-6(-8r-6)=-30 | | 9n+36=57 | | 1/2(3+9)=h | | 4x-12=3x=18=20 | | A=1/2(3+9)h | | −9x+27=108 | | 9.38=3.5+1.2(6.3–7x) | | 3x-3=26 | | 68.88=1.99-45x | | y–417=13 | | =3q+2 |